The Winding Road to Return to the Beauty of Indonesian Multiculturalism: A Discourse Analysis of ‘Back to Nagari’ in the Regional Autonomy Policy in West Sumatra - Hasanuddin Hasanuddin; Akmal Akmal; Welhenderi Azwar; Handoko Handoko (JURNAL ARBITRER, 2023)
The plurality of Indonesia with more than 600 ethnics is a great wealth but has not been adequately rewarded. Various political, legal, and socio-cultural events have resulted in the degradation of diversity from a colorful mosaic to a blur. This article analyzes the discourse of ‘return to nagari’ based on texts of national commitments and policies on decentralization, West Sumatra’s local policies on the lowest government ‘nagari’, and public responses on them. The methods had been used are literature study and field research, which are analyzed based on the technique of discourse analysis which included text, context, and social practice. The findings are the policy on decentralization is still inconsistent, and the construction of the regional government’s policy based on local culture has not been ideal and operational formulated yet. In fact, it is not easy to return to indigenous culture as roots the Beauty of Indonesia’s Multiculturalism. This finding reflects the critical implication of the discursive practice that shows the awareness of actor’s membership in their culture that leads them to make clear cultural-political attitudes in relation to the state. The position of their cultural traditions is threatened and our position is to mobilize them to revive, maintain, keep, consolidate and revitalize their cultural identity.